(i) Given
"\\frac{dy}{dx} - y = 3te^{2t}" with "y(0) = 1"
Solving the differential equation,
Equation is linear in y and first order equation.
Integral factor will be "e^{ - \\int dt} = e^{-t}"
multiplying this factor on both sides of equation,
"e^{-t}(\\frac{dy}{dx} - y) = 3te^{2t}e^{-t}"
"e^{-t}(\\frac{dy}{dx} - y) = 3te^{t}"
Now integration both sides with respect to x,
"e^{-t}y = \\int 3te^{t}dt"
"e^{-t}y = 3[te^{t} - \\int e^{t} dt]"
"e^{-t}y = 3[te^{t} -e^{t}]" "+ c"
"e^{-t}y = 3e^{t}(t-1) + c"
so "y = 3e^{2t}(t-1)+ce^{t}"
applying condition, "y(0) = 1,"
"1 = -3 +c\\implies c=4"
so equation will be
"y = 3e^{2t}(t-1) + 4 e^t"
(ii) "\\frac{dy}{dx} = (1-11x)y^2" with "y(0) = \\frac{-1}{6}"
integrating both sides
"\\int \\frac{dy}{y^2} = \\int (1-11x)dx"
"\\frac{-1}{y} = x - \\frac{11}{2}x^2 + c"
applying condition "y(0) = \\frac{-1}{6}"
then "6 = 0 - 0 +c \\implies c = 6"
then equation will be
"\\frac{-1}{y} = x - \\frac{11}{2}x^2 + 6"
"\\frac{-1}{y} = \\frac{2x - 11x^2 + 12}{2}"
then "{y} = \\frac{-2}{2x - 11x^2 + 12}"
Comments
Leave a comment